A dynamic systems methodological approach to understanding the collaborative nature of joint attention in early childhood settings. Issue 4 (December 2022) - Jacobson, Sarah; Degotardi, Sheila
In this article, we present a dynamic systems theoretical and methodological approach to investigating joint attention in early childhood (EC) centres. Joint attention, defined as a social interaction in which child and caregiver share a common focus of attention, is an important interactive context for collaborative learning. We overview the principles of dynamics systems theory and explain how these principles conceptualise joint attention as emerging from synchronised, 'in-the-moment' interactions between child and educator. Drawing on data from a project investigating the dynamic nature of joint attention in infant EC rooms, state space grids (SSGs) are then presented as a research tool that graphically captures and represents the mutually influencing contributions of educator, infant and the environment. We conclude by considering other ways to use SSG analysis to provide a more nuanced understanding of the dynamics of educator child interactions in EC settings.